Frequent psychological damage in girls, boys and adolescents who are victims of sexual abuse”. Analysis of cases treated at the Victims Assistance Center of the Public Ministry of Concepción. (Legal journal - Research in Legal and Social Sciences, 2017)
This research aims to identify the psychological damage that may occur more frequently in victims of sexual abuse treated at the Victims Care Center of the Department of Concepción in the period 2014-2015. It is intended to identify the behaviors acquired by people (boys and girls) who have suffered sexual abuse, as well as to determine the way in which the loss of trust towards the aggressor, the environment and its development in the context of interpersonal relationships is evidenced. In this order of ideas, the factors that allow visualizing the reactions of the victims who feel labeled or stigmatized by the act suffered will be identified, define how the victim reacts to the various situations that he could experience and use the procedures planned to avoid re-victimization in cases of sexual abuse of boys and girls. The work has a statistical analysis of the cases attended during the period 2014 - 2015 (until May 32), of which the psychological damage of the victims was analyzed and it was established as a hypothesis that the victims of sexual abuse attended in the Victims Care Center of the department of Concepción in the period 2014-2015 present psychological damage as a result of sexual abuse.
Keywords: victims; joint teams; human trafficking; behaviors; sexual abuse; stigmatization; psychological damage; sequelae